2019
DOI: 10.1016/j.heliyon.2019.e01484
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Progressive Muscle Relaxation – A systematic review of effectiveness

Abstract: Objective We perform a systematically search, appraise and synthesize of the best available evidence on the effectiveness of Progressive Muscle Relaxation (PMR) in the adults with schizophrenia, in any setting, regarding anxiety, personal and social functioning, cognition, and well-being. Method Major databases were searched to find both published and unpublished studies from inception until April 2017, using Schizophren* AND Relax* as keywords, and studies published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…out of 1172 selected studies retained 05 studies which showed (on 216 patients) a significant improvement on anxiety, well-being and social functioning. These results were achieved through progressive muscle relaxation (PMR) [ 8 ]. Lastly, in Taiwan [ 9 ], 80 patients in a psychiatric ward were separated into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…out of 1172 selected studies retained 05 studies which showed (on 216 patients) a significant improvement on anxiety, well-being and social functioning. These results were achieved through progressive muscle relaxation (PMR) [ 8 ]. Lastly, in Taiwan [ 9 ], 80 patients in a psychiatric ward were separated into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are several kind of relaxation methods, namely: (1) muscle relaxation, (2) diaphragmatic breathing, (3) imagery training, (4) biofeedback, and (5) hypnosis 12 . Progressive muscle relaxation is the cheapest method of relaxation, requires no imagination, has no side effects, is easy to do, and can make the body and mind feel calm, relaxed, and easier to sleep 13 . A previous study reported that progressive muscle relaxation can improve the sleep quality in patients undergoing hemodialysis 13 .…”
Section: Progressive Muscle Relaxation (Pmr) Is One Way To Improve Ph...mentioning
confidence: 99%
“…During that time, participants do not practice the PMR techniques, thus the effects obtained from PMR may have subsided by then. Nonetheless, PMR may be useful to decrease state anxiety, improve well-being and social functioning in adults especially with clinically mental illness (Melo-Dias et al, 2019).…”
Section: Ijphcsmentioning
confidence: 99%